Tinjauan Hukum Islam Terhadap Istri Yang Memilih Berkarir - Rendra, Robi (LPPM UNIVERSITAS Pertiba Pangkalpinang, 2023)
This study aims to review Islamic law on wives who choose a career in their daily activities. This study used a normative qualitative method. It used both primary data and secondary data. Data analysis used the descriptive analysis method. The results of this study showed that scholars have different opinions about wives who choose careers. Indeed, there is no explicit prohibition in Islamic teachings about wives who choose a career and work outside the house both in stable and unstable family economic conditions. Moreover, referring to the Islamic teachings, wives who choose a career have to pay attention to the boundaries and rules of Islamic teachings. Besides, they have to maintain their honor and dignity as female Muslims so that it does not conflict with their nature as a woman.